Management of radiation safety by optimizing the parameters of protective structures - Mamontov, O.V.; Malyk, B.O.; Tokarieva, О.V. (Вопросы атомной науки и техники, 2020)
The task of radiation safety management by the optimization of protective structures parameters has been considered. The techniques for calculating the attenuation coefficient of radiation of multilayer floor slabs, the range of constructional materials and the method of the optimization calculation of multilayer protective structures have been analyzed. The analysis has shown that the achievement of the maximum possible efficiency of protection at random distribution of materials is improbable. The optimization task has been solved of the distribution of materials on protective structures and their constructional elements and the list of target functions and restrictions has been made. The algorithm and the program have been developed, the method of optimization calculation of a group of protective structures for the purpose of increasing personnel radiation safety has been improved, and the calculation data testifying the efficiency of the offered approach have been obtained. Розглянуто задачу управління радіаційною безпекою шляхом оптимізації параметрів захисних споруд. Проаналізовано методики розрахунку коефіцієнта ослаблення радіації багатошарового перекриття, ряд конструкційних матеріалів і метод оптимізаційного розрахунку багатошарових захисних конструкцій. Показано, що досягнення максимально можливої ефективності захисту від іонізуючого випромінювання, в тому числі гамма-випромінювання, при випадковому розподілі матеріалів малоймовірно. Розв'язана задача оптимізації розподілу матеріалів по спорудах і їх конструктивних елементів, розглянуто перелік цільових функцій і обмежень. Розроблено алгоритм і програма, удосконалено метод оптимізаційного розрахунку групи споруд з метою підвищення радіаційної безпеки персоналу, отримані розрахункові дані, що свідчать про ефективність запропонованого підходу. Рассмотрена задача управления радиационной безопасностью путем оптимизации параметров защитных сооружений. Проанализированы методики расчета коэффициента ослабления радиации многослойного перекрытия, ряд конструкционных материалов и метод оптимизационного расчета многослойных защитных конструкций. Показано, что достижение максимально возможной эффективности защиты от ионизирующего излучения, в том числе гамма-излучения, при случайном распределении материалов маловероятно. Решена задача оптимизации распределения материалов по сооружениям и их конструктивным элементам, рассмотрен перечень целевых функций и ограничений. Разработаны алгоритм и программа, усовершенствован метод оптимизационного расчета группы сооружений с целью повышения радиационной безопасности персонала, получены расчетные данные, свидетельствующие об эффективности предложенного подхода.